Pengaruh Ukuran Pemerintah Dearah, Belanja Modal, Dana Perimbangan, Dan Pendapatan Asli Daerah Terhadap Kinerja Keuangan Pemerintah Daerah Kota/Kabupaten Di Provinsi Bali - Made Ayu Mira Mahadewi; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2023)
This study aims to examine the effect of the size of the local government, capital expenditures, balancing funds and local revenue (PAD) on the financial performance of local governments in the province of Bali for the period 2017 to 2020.The population in this study is all regencies/cities of the province consisting of nine regencies. in the Province of Bali. The nine objects were observed for five periods (2017-2020). The sample used is 36 districts in the province of Bali. By using the saturated sampling method. Data obtained through the LRA report and balance sheet using non-participant observation methods as data collection which will later be processed so that it does not require a questionnaire (list of questions). from the research results it is reflected that the increasing size of government will have an impact on decreasing financial performance. Capital Expenditures have no relation to Financial Performance measures. Balancing Funds are negatively related to Financial Performance. PAD does not directly affect Financial Performance.